Estimating Young’s Modulus of Materials by a New Three-Point Bending Method - Xiaohu Zeng; Shifeng Wen; Mingxi Li; Gongnan Xie (Advances in Materials Science and Engineering)
A new test method based on the three-point bending test is put forward to measure Young’s modulus of materials. The simplified mechanical model is established to make theoretical derivation. This method has not only the advantages of simple specimen preparation and convenient loading device, but also higher precision than the traditional three-point bending method. The method is adopted to obtain Young’s modulus of the aluminum alloy 2024. The feasibility of the method has been demonstrated by comparisons with the corresponding results obtained from the finite element method and experiment method. And the influence of contact friction on the test accuracy is analyzed.